Trajectory planning of an end-effector for path with loop - Boryga, Marek (Strojniški vestnik, 2014)
This paper presents an algorithm for rectilinear-arc trajectory planning whose path is composed of two rectilinear segments connected with a loop-shaped arc. The algorithm can be used in solutions with high speed cornering applications. During the realization of the given trajectory, the end-effector passed through the corner twice and the time difference is, simultaneously, the time of loop tracking. On the rectilinear segments, end-effector acceleration was described by a 7th degree polynomial, whereas the velocity while moving through a loop was a constant value. The results of the trajectory planning are presented as courses of displacements, speeds and accelerations of the end-effector and displacements, speeds and accelerations in kinematic pairs of the three manipulators
Keywords: antropomorfni manipulator; kartezični manipulatorji; manipulatorji SCARA; načrtovanje trajektorije; ostri ovinki; polinomski profil pospeška; pot z zanko